Combined Partial Denitrification (PD)-Anammox: A method for high nitrate wastewater treatment. (May 2019) - Du, Rui; Cao, Shenbin; Peng, Yongzhen; Zhang, Hanyu; Wang, Shuying
Abstract: Elimination of nitrogen pollution from wastewater containing high-strength nitrate (NO3 − -N) is a significant issue to prevent deterioration of water quality and eutrophication of receiving water body. Traditional denitrification process faces several challenges including the huge organic carbon demand, intermediate products accumulation, and long acclimatization period. In this study, an efficient solution was given by a novel two-stage Partial Denitrification (PD)-Anammox process. High NO3 − -N (1000 mg N/L) wastewater and municipal sewage (COD: 182.5 mg/L, ammonia (NH4 + -N): 58.3 mg/L) were simultaneously introduced to the PD reactor for NO3 − -N converting to NO2 − -N. The NH4 + -N and NO2 − -N in effluent of PD were removed in subsequent anammox reactor. Results showed that a satisfactory nitrogen removal was achieved by optimizing the volume ratios of influent NO3 − -N and municipal sewage, as well as the external organic matter dosage. The NO3 − -N removal efficiency reached up to 95.8% without accommodation period, along with the NH4 + -N removal achieving 92.8%. Anammox contributed to 78.9% of TN removal despite the high COD (76.5–98.6 mg/L) in PD effluent was introduced, indicating the significant stability of the integrated process. The microbial analysis suggested that the Candidatus Brocadia, identified as anammox bacteria, cooperated stable with denitrifying bacteria in 215-day operation. The PD-Anammox process offers an economically and technically attractive approach in the high NO3 − -N wastewater treatment since it has great advantages of much low carbon demand, minimal sludge production, enabling simultaneous treatment of municipal sewage, and avoiding the common issues in traditional denitrification process. Graphical abstract: Unlabelled Image Highlights: Simultaneous treatment of high-strength nitrate and municipal sewage was demonstrated. Nitrate removal efficiency reached up to 95.8% at influent nitrate of 1000 mg/L. Municipal sewage was treated with nitrogen removal efficiency of 92.8%. Anammox and denitrifying bacteria cooperated for advanced nitrogen removal. Partial-denitrification combining with anammox is an economic and efficient option.